Improving agricultural productivity in Papua New Guinea: Strategic and policy considerations - Benny, Dickson; Benson, Todd; Ivekolia, Mark; Kedir Jemal, Mekamu; Ovah, Raywin (International Food Policy Research Institute, 2022)
If smallholder farming households in Papua New Guinea achieve higher crop productivity levels, progress will be made along several dimensions of the development vision for PNG – increasing GDP for the agricultural sector and the overall economy; driving growth, diversification, and transformation of local rural economies; improving food consumption; and reducing poverty. In this paper, we examine recent data on yields for the most important crops grown in PNG, assess what yields might be achieved based on productivity data from areas of Indonesia with similar growing conditions, and sketch where policy reforms could provide incentives and access to technologies to achieve higher crop yields by all farmers across PNG.